Mathematics Learning Improvement Through Example-Non-Example with Flannel Board: Peningkatan Pembelajaran Matematika Melalui Contoh dan Non-Contoh dengan Papan Flanel - Gusta Rahadi; Nurlev Avana; Apdoludin (Academia Open, 2025)
General Background: Mathematics is a compulsory subject in Indonesian primary education as it develops logical reasoning and problem-solving skills, yet many students face difficulties due to monotonous teaching approaches. Specific Background: Preliminary observations in grade III of SDN 11/II Teluk Pandak revealed only 30.43% of students achieved the minimum mastery criteria, largely due to low engagement and ineffective instructional strategies. Knowledge Gap: While previous studies have shown the benefits of Example Non-Example models and flannel board media separately, limited research has examined their combined application in elementary mathematics learning. Aims: This study aimed to improve students’ mathematics learning processes and outcomes by integrating the Example Non-Example model with flannel graph media. Results: Using classroom action research across two cycles, findings demonstrated significant improvement, with student mastery increasing from 30.43% (pre-cycle) to 56.52% (cycle I) and 91.30% (cycle II). Novelty: The strategic integration of visual-conceptual learning through Example Non-Example with interactive flannel media offers a more engaging and contextualized learning experience. Implications: These findings suggest that combining innovative instructional models with concrete media can foster active participation, enhance conceptual understanding, and serve as a practical strategy for improving mathematics education in elementary schools.Highlight : Model Example Non-Example with flannel graph improved mathematics learning outcomes. Student achievement increased significantly from cycle I to cycle II. Learning became more active, engaging, and effective. Keywords : Learning Process, Learning Outcomes, Example Non-Example, Flannel Graph, Mathematics